PENGARUH HARGA, LOKASI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAYBELLINE (Studi Pada Konsumen Maybelline Paragon Mall Semarang) - Iwang Adhi Suryawan; Sudharto Prawata Hadi (Universitas Diponegoro, 2024)
Abstract Purchasing decisions are consumer decisions with economic, financial, technological, political, cultural, product, price, and location considerations before finally deciding to purchase a product or use a service. The purpose of this research is to find out how far the price, location and brand image influence the purchasing decision. The object of research in this study is a beauty product with the brand